Pelatihan implementasi buku sains dengan pendekatan case-based learning untuk peningkatan berpikir kritis mahasiswa PGSD - Fembriani, Fembriani; Lehan, Andriyani Dua; Netty Elisabeth , A Nawa (Nur Science Institute, 2025)
Training on implementing science books using a Case-Based Learning (CBL) approach was conducted to enhance students' critical thinking skills. This training was motivated by the need for innovative teaching materials that are not only theoretical but also able to present real-world contexts in science learning. The training was carried out in several stages: an introduction to the concept of CBL, guidance on using case-based science books, and direct practice during the learning process. The participants were students of the Elementary School Teacher Education study program in the Basic Concepts of Science course. The instruments used included a response questionnaire, observations of the training implementation, and a test. The results showed that implementing science books with a CBL approach had a positive impact, as evidenced by improvements in students' ability to identify problems, analyse information, and draw logical conclusions from real cases. In addition, students' responses to the training were also very positive, with evaluations indicating that CBL-based science books are practical and engaging. The posttest results showed an improvement in students' critical thinking, with an average score of 82. Thus, training in implementing CBL-based science books proved effective in equipping students for science learning.